Effective Factors on Dominant Diets among Adults in Gonabad City - Maryam Esmaeili; Mojtaba Kianmehr; Hamid Rasekhi; Amirhosein Basirimoghadam; Mehrdad Kianmehr; Mustafa Pouryousef; Maryam Eskafi-Noghani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background & Objective: Proper nutrition is a very important factor in maintaining and promoting health and its role has been proven to be a determining factor in chronic diseases. To better understand the relationship between nutrition and diseases, it is best to consider nutrition as a diet and identify the factors associated with it. This study tended to determine the factors related to the dominant diets (demographic, social, economic, anthropometric and physical activity factors) in adults in Gonabad. Materials & Methods: This cross-sectional study was performed in 2019 on adults in Gonabad. The sampling method was random stratified. The instruments used in this study were the Food Frequency Questionnaire, the Baecke Physical Activity Questionnaire, and scale and measuring tape. Exploratory factor analysis was used to identify the dominant diets. Independent T-tests, analysis of variance, chi-square and multiple regression were used to determine the factors associated with diets. Data was analyzed using SPSS software version 14.5 (p<0.05).Results: The results showed a statistically significant relationship between unhealthy diet with age (p<0.001), gender (p=0.015), job (p=0.025), number of family members (p=0.038), income (p=0.001), waist circumference (p=0.013) and physical activity (p=0.002). These variables predict a total of 17.6% of variance in unhealthy diet. Moreover, there was a statistically significant relationship between healthy diet and age (p<0.001), number of family members (p=0.015), waist circumference (p<0.001) and physical activity (p=0.0288). These variables predict a total of 32.7% variance in healthy diet.Conclusion: In general, the results of this study show that demographic, social, economic, anthropometric and physical factors play an important role in determining the type of dominant diet.